Geometric C1+α regularity estimates for nonlinear evolution models. (July 2019) - da Silva, João Vitor
Abstract: In this survey we establish geometric C 1 + α regularity estimates for bounded solutions of a number of nonlinear evolution models in divergence and non-divergence form. The main insights to obtain such estimates are based on geometric tangential methods, and make use of systematic oscillation mechanisms combined with intrinsic scaling techniques.